[Ag115S34(SCH2C6H4tBu)47(dpph)6]: synthesis, crystal structure and NMR investigations of a soluble silver chalcogenide nanocluster12. Issue 3 (15th December 2016) - Bestgen, Sebastian; Fuhr, Olaf; Breitung, Ben; Kiran Chakravadhanula, Venkata Sei; Guthausen, Gisela; Hennrich, Frank; Yu, Wen; Kappes, Manfred M.; Roesky, Peter W.; Fenske, Dieter
Abstract : The soluble 115 nuclear silver cluster [Ag115 S34 (SCH2 C6 H4 t Bu)47 (dpph)6 ] was synthesized and fully characterized in solution and in the solid state. Abstract : With the aim to synthesize soluble cluster molecules, the silver salt of (4-( tert -butyl)phenyl)methanethiol [AgSCH2 C6 H4 t Bu] was applied as a suitable precursor for the formation of a nanoscale silver sulfide cluster. In the presence of 1, 6-(diphenylphosphino)hexane (dpph), the 115 nuclear silver cluster [Ag115 S34 (SCH2 C6 H4 t Bu)47 (dpph)6 ] was obtained. The molecular structure of this compound was elucidated by single crystal X-ray analysis and fully characterized by spectroscopic techniques. In contrast to most of the previously published cluster compounds with more than a hundred heavy atoms, this nanoscale inorganic molecule is soluble in organic solvents, which allowed a comprehensive investigation in solution by UV-Vis spectroscopy and one- and two-dimensional NMR spectroscopy including 31 P/ 109 Ag-HSQC and DOSY experiments. These are the first heteronuclear NMR investigations on coinage metal chalcogenides. They give some first insight into the behavior of nanoscale silver sulfide clusters in solution. Additionally, molecular weight determinations were performed by 2D analytical ultracentrifugation and HR-TEM investigations confirm the presence of size-homogeneous nanoparticles present in solution.